2013
DOI: 10.1021/la400452e
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Kinetics of Sessile Water Droplets on Micropillared Superhydrophobic Surfaces

Abstract: Evaporation modes and kinetics of sessile droplets of water on micropillared superhydrophobic surfaces are experimentally investigated. The results show that a constant contact radius (CCR) mode and a constant contact angle (CCA) mode are two dominating evaporation modes during droplet evaporation on the superhydrophobic surfaces. With the decrease in the solid fraction of the superhydrophobic surfaces, the duration of a CCR mode is reduced and that of a CCA mode is increased. Compared to Rowan's kinetic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
132
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 60 publications
9
132
1
Order By: Relevance
“…9 6 3.4 . This stick-slip phenomenon 26 is characteristic of the sparser pillar geometry in the CCA mode. Near the end of evaporation (s % 0.90), the droplet returns to the mixed mode, and at s % 0.96, the contact radius experiences a sudden increase, signifying that the droplet has been impaled by the pillars and displaced the air gaps, entering the Wenzel state.…”
Section: Effect Of Superhydrophobic Surface Morphology On Evaporativementioning
confidence: 92%
See 2 more Smart Citations
“…9 6 3.4 . This stick-slip phenomenon 26 is characteristic of the sparser pillar geometry in the CCA mode. Near the end of evaporation (s % 0.90), the droplet returns to the mixed mode, and at s % 0.96, the contact radius experiences a sudden increase, signifying that the droplet has been impaled by the pillars and displaced the air gaps, entering the Wenzel state.…”
Section: Effect Of Superhydrophobic Surface Morphology On Evaporativementioning
confidence: 92%
“…In recent studies, [23][24][25] the droplet evaporation rate was reported to be reduced on superhydrophobic surfaces due to increased influence of evaporative cooling at the droplet interface. Three modes of droplet evaporation on superhydrophobic surfaces have been reported 20,26,27 as well: a constant contact radius (CCR) mode, a constant contact angle (CCA) mode, and a mixed mode. In the CCR mode, the contact line remains pinned while the contact angle decreases, whereas in the CCA mode, the contact angle remains fixed as the contact line recedes.…”
Section: Effect Of Superhydrophobic Surface Morphology On Evaporativementioning
confidence: 99%
See 1 more Smart Citation
“…For simple liquids this stage is very fast and evaporation can be neglected during it, therefore in most studies it is out of consideration and only three consequent stages of evaporation are taken into account [31*-33*]. It is noteworthy that the mentioned stages of evaporation were observed on substrates of various wetting properties including superhydrophobic micropillar-patterned ones [34]. During the first stage of evaporation the drop base radius remains constant, whereas the contact angle decreases to the value of receding contact angle.…”
Section: Convection In the Vapour Phasementioning
confidence: 99%
“…[1][2][3][4][5] There has been considerable focus on understanding their wettability 6,7 and developing them for a wide range of applications including droplet impact resistance, [8][9][10][11][12][13] anti-icing, [14][15][16][17][18][19] dropwise condensation, [20][21][22][23][24] electro-wetting, 25,26 drag reduction, [27][28][29][30][31][32] evaporation, 33,34 and anti-corrosion. [35][36][37][38] An important challenge for broad applicability of these hydrophobic materials is their limited robustness.…”
mentioning
confidence: 99%